2000
DOI: 10.21273/hortsci.35.5.882
|View full text |Cite
|
Sign up to set email alerts
|

Control of Bacterial Spot on Tomato in the Greenhouse and Field with H-mutant Bacteriophages

Abstract: A mixture of host-range mutant (h-mutant) bacteriophages specific for tomato race 1 (T1) and race 3 (T3) of the bacterial spot pathogen, Xanthomonas campestris pv. vesicatoria (Doidge) Dye was evaluated for biological control of bacterial spot on `Sunbeam' tomato (Lycopersicon esculentum Mill.) transplants and field-grown plants for two seasons (Fall 1997 and Fall 1998). Foliar applications of bacteriophages were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 8 publications
0
67
0
Order By: Relevance
“…Recently, some biological methods were used successfully to control tomato bacterial diseases (Flaherty et al, 2000;Louws et al, 2001;Balogh et al, 2003;Obradovic et al, 2005;Ji et al, 2006). Among biological control methods, endophytic bacteria are also one of the most reliable and ecologically as well as economically sustainable alternatives to chemical pesticides (Klopper et al, 1999;Rajendran et al, 2006Rajendran et al, , 2007Ryan et al, 2008;Nagendran et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some biological methods were used successfully to control tomato bacterial diseases (Flaherty et al, 2000;Louws et al, 2001;Balogh et al, 2003;Obradovic et al, 2005;Ji et al, 2006). Among biological control methods, endophytic bacteria are also one of the most reliable and ecologically as well as economically sustainable alternatives to chemical pesticides (Klopper et al, 1999;Rajendran et al, 2006Rajendran et al, , 2007Ryan et al, 2008;Nagendran et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the use of bacteriophages is another form of biological control and has been successful for managing several annual plant diseases (Jones et al 2007(Jones et al , 2012. Phages were reported to have a high degree of specificity against P. syringae disease on tomato (Cupples 1983;Flaherty et al 2000). The authors indicated that these phages lysed 90 % of the virulent tomato strains tested.…”
Section: Exclusion Elimination or Reduction Of Pathogen Inoculummentioning
confidence: 99%
“…vesicatoria which is responsible for leaf spot disease on peppers and tomatoes (Flaherty et al, 2000;Obradovic et al, 2004), Xanthomonas campestris pv. pelargonii causing bacterial blight in geraniums (Flaherty et al, 2001), Xanthomonas axonopodis pv.…”
Section: Accepted Manuscriptmentioning
confidence: 99%